2012
DOI: 10.1111/ijcp.12075
|View full text |Cite
|
Sign up to set email alerts
|

Current perspectives in bladder cancer management

Abstract: Summary More than 350,000 new cases of bladder cancer are diagnosed worldwide each year; the vast majority (> 90%) of these are transitional cell carcinomas (TCC). The most important risk factors for the development of bladder cancer are smoking and occupational exposure to toxic chemicals. Painless visible haematuria is the most common presenting symptom of bladder cancer; significant haematuria requires referral to a specialist urology service. Cystoscopy and urine cytology are currently the recommended tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
88
0
12

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(100 citation statements)
references
References 117 publications
0
88
0
12
Order By: Relevance
“…Each year more than 350,000 new cases of bladder cancer are diagnosed globally (1), making bladder cancer the ninth most frequent cancer worldwide (2). Epirubicin (EPI) and pirarubicin (THP) are a new generation of anthracycline drugs, widely used as anticancer chemotherapeutic agents in various types of cancers including bladder cancer (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Each year more than 350,000 new cases of bladder cancer are diagnosed globally (1), making bladder cancer the ninth most frequent cancer worldwide (2). Epirubicin (EPI) and pirarubicin (THP) are a new generation of anthracycline drugs, widely used as anticancer chemotherapeutic agents in various types of cancers including bladder cancer (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…In the EMPA-REG OUTCOME trial, cases of bladder cancer were identified from adverse events coded using the following preferred terms in the Medical Dictionary for Regulatory Activities (MedDRA): 'bladder cancer'; 'bladder cancer recurrent'; 'bladder cancer transitional cell carcinoma'; and 'transitional cell carcinoma'. Transitional cell carcinoma accounts for over 90% of all bladder cancers [3]. Documentation relating to events coded as transitional cell carcinoma was medically reviewed and cases confirmed.…”
Section: Sglt2 Sodium-glucose Cotransportermentioning
confidence: 99%
“…Animal studies show that the risk of cyclophosphamide-induced bladder cancer is significantly lower when the treatment is accompanied by the administration of Mesna (sodium 2-mercaptoethanesulphonate) [66].…”
Section: Mesna (Sodium 2-mercaptoethanesulfonate)mentioning
confidence: 99%